MODEL OF AN INTEGRATED ENVIRONMENTAL SAFETY SYSTEM FOR CONSTRUCTION - A. L. Bolsherotov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Every year, environmental issues are becoming more and more critical. Experts predict no more than ten years of reaching the point of no return when environmental problems will move into a phase of uncontrolled chaos. Most often, catastrophic changes are associated with climate warming due to greenhouse gas emissions from industry and transport. However, the root cause of everything, as established in the research by Slesarev et al., is the construction industry as the primary source of environmental problems. The problem of environmental safety especially concerns cities and large settlements. The conducted research has established that environmental safety is determined as the sum of the impacts of construction projects on a unit area of residential territory. For an objective assessment of environmental safety, environmental pollution, the impact of various factors, and the resulting effect of the indirect impact of construction projects on the environment were considered. Methods. New conceptual approaches and principles were applied in assessing the environmental safety of construction sites and territories, taking into account the current environmental status of the built-up areas, which makes the problem of environmental safety manageable, and provides  modern and future generations with health, a comfortable environment, and health. Results. As a result of process modeling, the "real estate concentration degree" ratio was adopted as an integrating concept of environmental safetyof the area, and the concepts of "environmental reserve," "environmental safety threshold," and "sustainable state range" were introduced. The stability ratio concept (rstab) is introduced, a method for calculating this  ratio is developed to assess the range of the sustainable environment state – the magnitude of the variation in the size of the ecological reserve depending on climatic conditions, time of day, week, year. As a result, the numerical values of the above-mentioned indicators for the studied areas are obtained. As the main document reflecting the state of the environmental safety of the construction object, the development of the environmental  facility certificate and the environmental area certificate is proposed. To create an environmental certificate, the structure of environmental safety  has been developed and justified, which includes four main blocks: external  environmental safety, internal environmental safety, energy efficiency, and  autonomy of the facility (area).Conclusion. The proposed approach to the assessment of environmental safety makes it possible to reliably assess the possibilities of areas for the placement of construction projects with various industry-related potential, plan measures to ensure a range of sustainable conditions of the  areas, which ultimately ensures the quality of life and health of the population, a comfortable and safe environment of residential areas, as well as the wildlife preservation.